2016
DOI: 10.1074/mcp.m115.052498
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Proteomic and Metabolomic Signatures of Nontypeable Haemophilus influenzae-Induced Acute Otitis Media Reveal Bacterial Aerobic Respiration in an Immunosuppressed Environment

Abstract: A thorough understanding of the molecular details of the interactions between bacteria and host are critical to ultimately prevent disease. Recent technological advances allow simultaneous analysis of host and bacterial protein and metabolic profiles from a single small tissue sample to provide insight into pathogenesis. We used the chinchilla model of human otitis media to determine, for the first time, the most expansive delineation of global changes in protein and metabolite profiles during an experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 150 publications
1
18
0
Order By: Relevance
“…7 ). Similarly, we have previously shown that inhibition of the actin-related protein complex Arp2/3 prevents NTHI uptake into epithelial cells ( 70 ). Therefore, it is tempting to speculate that the use of macropinocytosis or actin inhibitors could prevent NTHI persistence and reduce recurrent episodes of OM.…”
Section: Discussionsupporting
confidence: 55%
“…7 ). Similarly, we have previously shown that inhibition of the actin-related protein complex Arp2/3 prevents NTHI uptake into epithelial cells ( 70 ). Therefore, it is tempting to speculate that the use of macropinocytosis or actin inhibitors could prevent NTHI persistence and reduce recurrent episodes of OM.…”
Section: Discussionsupporting
confidence: 55%
“…This model provides a new platform for the identification of novel diagnostic and therapeutic approaches for OM. Our prior proteomic studies demonstrate an increase in the actin filament branching protein, Arp2/3, during acute experimental OM and that inhibition of Arp2/3 decreases NTHI invasion as a potential adjunct therapy [ 64 ]. Finally, it is of interest to determine whether intracellular populations contribute to the other NTHI-mediated diseases such as conjunctivitis, sinusitis, pneumonia, and exacerbations in COPD and cystic fibrosis [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…On days 7, 14, and 28, chinchillas were sacrificed and the middle ears removed, fixed in 4% paraformaldehyde in Dulbecco鈥檚 Phosphate Buffered Saline (DPBS), decalcified in 0.35 M Tris/EDTA solution and embedded in paraffin. Thin sections from fixed middle ears were deparaffinized in xylene and antigen-retrieval was performed as previously described [ 64 ] followed by treatment with 0.01% sodium borohydride (Thermo Fisher Scientific) in DPBS for 10 minutes to inhibit inherent fluorescence due to aldehyde production. Slides were then incubated for 10 minutes in CAS Block (Thermo Fisher Scientific) to prevent non-specific staining followed by a 30-minute incubation with Image-iT FX Signal Enhancer (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that nutritional sequestration influences disease progression and severity, microevolution of NTHI during stationary phase, and establishment of an intracellular NTHI population Szelestey et al, 2013). Host microenvironmental influences on NTHI pathoadaptation and evolution have revealed additional targets for treatment of OM based upon the multiple pathogenic lifestyles revealed in our studies (e.g., biofilm, intracellular) Harrison et al, 2016;Szelestey et al, 2013). In order to evaluate the effect of multiple episodes of OM on the microevolution of NTHI, we established a model system of sequential OM episodes through naive hosts.…”
Section: Introductionmentioning
confidence: 59%